Dealloyed PdAg core Pt monolayer shell electrocatalyst for oxygen reduction reaction. Issue 21 (9th February 2016) - Yang, Hai-Fang; Feng, Yuan-Yuan; Du, Li-Xia; Liu, Zeng-Hua; Kong, De-Sheng
Abstract : A core–shell nanostructure with dealloyed PdAg nanoparticles as the core and a Pt monolayer as the shell shows much higher catalytic properties for oxygen reduction reaction as compared with its counterpart with alloyed PdAg as the core. Abstract : A core–shell nanostructure (Pt–PdAg/C–D) with dealloyed PdAg nanoparticles (PdAg/C–D) as the core and a Pt monolayer as the shell is prepared and employed as an electrocatalyst toward oxygen reduction reaction (ORR). Compared with its counterpart alloyed PdAg core-Pt monolayer shell catalyst (Pt–PdAg/C), the Pt–PdAg/C–D catalyst shows significantly higher catalytic activities for ORR. The half wave potential ( E 1/2 ) on Pt–PdAg/C–D is located at −0.17 V, which is comparable to that on the commercial Pt/C catalyst and ca. 30 mV more positive than that on Pt–PdAg/C. The MSA of Pt in Pt–PdAg/C–D is 171.8 A gPd+Pt −1, which is 3.2 and 2.4 times higher than those of Pt–PdAg/C and commercial Pt/C catalysts, respectively. The Pt monolayer shell on the surface of the nanoparticles would induce much higher utilization of Pt atoms, and the dealloying process would result in a nanostructured PdAg core with a rough surface and a Pt shell with a numbers of low-coordinated atoms. It is concluded that the change in the electronic and geometric structure of Pt in the Pt–PdAg/C–D catalyst may contribute to the increase in catalytic performance for ORR.